Analisis Fundamental Makro dan Struktur Modal Terhadap Nilai Perusahaan dengan Variabel Intervening pada Perusahaan Sektor Industri Dasar dan Bahan Kimia Tahun 2018-2022 (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This research investigates how macroeconomic conditions and capital structure shape firm value, with particular attention to mediating influences specifically, ownership configuration, financial performance, earnings management practices, and intrinsic firm attributes. The empirical analysis draws on data from firms operating in the basic industry and chemical sectors, all publicly listed on the IDX between 2018 and 2022. Employing the PLS structural equation modeling approach via SmartPLS, the study yields several key insights: Macroeconomic indicators show no statistically significant association with firm attributes, financial outcomes, or earnings management behavior. Conversely, capital structure exerts a notable influence on earnings management strategies, though its effect on firm value operates exclusively through indirect pathways. Internal determinants including firm-specific traits and financial performance emerge as robust, positive drivers of firm valuation. Ownership configuration, however, demonstrates no direct linkage to either firm value or earnings management intensity. Collectively, the findings lend empirical support to both signaling theory and the trade-off theory of capital structure. They underscore a critical implication: enhancing internal governance frameworks, operational transparency, and corporate financial discipline contributes more substantially to firm value creation and the integrity of financial reporting than external macroeconomic fluctuations.